PENGUKURAN VOLUME SALIVA PADA PENERIMA RADIOTERAPI DAERAH KEPALA DAN LEHER DI RSUP HAJI ADAM MALIK MEDAN - fransiska banurea (Fakultas Kedokteran Gigi Universitas Sumatera Utara, 2013)
Abstract Radiotherapy of head and neck area may damage cancer cell, but it has side effect to damage healthy tissue, including salivary gland, thus it may cause the decreasing of salivary volume. Saliva is a complex fluid, consisting of secretion and gingival sulcus fluid, saliva is produced by major and minor salivary gland. Normal mean value of unstimulated salivary volume in healthy individual in a minute ranges between 0,25 - 0,35 ml. Due to radiotherapy of head and neck area occurs damage of ray cell mainly in parotid gland witch more radiosensitive characteristic to radiation, if inflammation becomes chronic will occur fibrosis in salivary gland that can cause the decreasing of salivary volume. This study aimed to measure salivary volume and to know the relation of salivary volume based on radiotherapy intensity in radiotherapy receiver of head and neck area at Central H. Adam Malik Hospital Medan. The study design used was Observational Analysis with Cross Sectional approach. This study was carried out in April – June 2012. Sample method selection was purposive sampling method. Salivary collection was done by spitting method and the mean value was measured then data analyzed with Anova test by using SPSS 17 program. The result of study in radiotherapy receiver of head and neck area at Central H. Adam Malik Hospital Medan was the mean value of highest salivary volume was on the group of 1 - 5 x radiotherapy intensity with mean±sd = 0.15060 ± 0.067818 ml/minute and was decreasing simultaneously until the lowest salivary volume on the group of 31 - 35 x radiotherapy intensity with mean±sd = 0.00840 ± 0.0066731 ml/minute.The result of study showed the decreasing of salivary volume due to side effect of head and neck radiotherapy . H0 was rejected in p < 0,05 it means that there were significant relations between radiotherapy intensity with the decreasing of salivary volume. Key words: Head and Neck Radiotherapy, Salivary Volume